Pamięć wielkiej wojny ojczyźnianej w narracjach młodzieży (Politeja, 2015)
The Great Patriotic War in Young People’s NarrativesThe present paper confronts the dual nature of the Great Patriotic War narrative − the official (collective) and the personal − young people’s memory of that war. The author, by pointing out the discrepancies between the official myth and individuals experience − as reconstructed by students based on their relatives’ narratives (grandmothers’ or grandfathers’) − emphasizes the importance of a personalized war experience pieced together by young people. She draws the reader’s attention to the de‑ideologization and the de‑composition of the ruling myth by young people. She discusses their attempts to make the official narrative more authentic − through the eyes of individual witnesses. She also emphasizes the students’ efforts to recover the memory of The Great Patriotic War exposing the elements outside the realm of mainstream remembrance propaganda. She stresses the fact that it is necessary for young people to endure the trauma of personal narratives.